Sostenibilidad ambiental y actividades de entretenimiento en la comunidad Galte Laime, parroquia Palmira, cantón Guamote, provincia de Chimborazo - Toaquiza Sinchiguano, Jefferson Ismael (2025)
The main objective of the research project is to analyze how environmental sustainability affects entertainment activities in the Galte Laime community, Palmira parish. The research methodology used was a quantitative and field approach; likewise, a transversal, descriptive, and exploratory approach was used for the research design. In addition, as a data collection technique, a survey was applied with its instrument, the questionnaire with the LIKERT scale. On the other hand, to solve the problem of the deficient development of entertainment activities, hypothesis tests were carried out to corroborate that entertainment activities do not have an impact on environmental sustainability, the results of which are given because the people in charge of the different means of entertainment have not been able to obtain a document where the negative impacts of the abuse of space for the various tourist activities are socialized. Finally, as a proposal, a guide of good practices for the development of entertainment activities was developed, offering a beacon of hope for the future of sustainability in tourism. The main objective of this guide is to mitigate the possible extinction of the animals that live in the tourist attraction and the destruction of the landscape.